Student Empowerment Through Multimedia-Based Business Strategy Seminars and Professional Portfolio Development - Nurdiansyah Permana; Muhammad Abdul Jabbar; Davit Hermawan; Fikri Akbar Falcata Winata; Sekar Fauzia Larasati (Community Service Journal : Jurnal Pengabdian Masyarakat Mardira, 2026)
In today’s rapidly evolving digital era, the ability to integrate technical multimedia skills with appropriate business strategies has become essential for enhancing the competitiveness of university graduates. However, challenges related to scheduling adjustments and internal coordination often hinder the effective implementation of educational activities among students.The “Creative Business” seminar was designed to provide in-depth insights into professional portfolio development, personal branding, and content monetization strategies for Multimedia students. This community engagement initiative was conducted through an educational seminar format, featuring both industry practitioners and academics as keynote speakers. The materials presented covered creative industry workflows, client management, and target market identification.The program successfully contributed to expanding participants’ knowledge of digital technology trends while also improving event management skills among the organizing committee. Despite encountering several technical issues, such as a schedule shift from 08:00 to 09:00 WIB and a change in the second speaker, participants responded positively to the clarity and relevance of the delivered content.Overall, the seminar proved effective in broadening students’ strategic perspectives. Nevertheless, incorporating more hands-on practice sessions and improving time management would further enhance the effectiveness of similar activities in the future.